Comparison of Physical Freshness Levels of SMP Negeri 6 Singingi Hilir with MTS S Masmur Pekanbaru City: Perbandingan Tingkat Kesegaran Jasmani SMP Negeri 6 Singingi Hilir Dengan MTSS Masmur Kota Pekanbaru - Ahmad Khoeri; M. Fransazeli (Jurnal Olahraga dan Kesehatan (ORKES), 2023)
The purpose of this study was to compare the level of physical fitness of Junior High School 6 Singingi Hilir with MTs S Masmur Pekanbaru City. The type of research used in this research is comparative research. The population in this study were all students of Junior High School 6 Singingi Hilir and students of MTs S Masmur Pekanbaru, while the sampling technique was using porposive sampling totaling 32 students of MTs S Masmur and 22 students of SMPN 6 Singingi Hilir. The test used in this study was the Indonesian Physical Fitness Test (TKJI). From the results of research and data analysis that has been put forward, the results obtained are t-count > t-table, namely (0.279) > 0.05, because tcount > T table. So, Ho is accepted. Thus, it can be concluded that there is a significant difference in the level of physical fitness between students at Junior High School 6 Singingi Hilir and MTs S Masmur Pekanbaru.